Penerapan Algoritma Rivest Shamir Adleman (RSA) untuk File Citra Menggunakan Visual Basic - Yessy Nazir; Arnellis Arnellis; Meira Parma Dewi (UNIVERSITAS NEGERI PADANG, 2019)
Abstract – Most images have important information or a secret message. Secret message can provoke onset of opportunity the existence of threats to change the message. The messages of the image can be done by manipulating or piracy on the image. The results of image manipulation can change the meaning the image. Such as threats can be avoided by providing a safeguard against the image. Application of Rivest Shamir Adleman (RSA) Algorithm for Image Files is one way to secure an image of piracy as well as the manipulation of images. This article discussed the application of the RSA algorithm for image files. This method can hide the image using an early form of the public key and return it to the initial form with private key. The whole process is done by using Visual Basic 6.0. On the various experiments conducted the results of his work from the encryption produces 13 imagery similar to the image of the beginning of 15 sample images. Errors may caused by the selection of keywords which is less precise. Keywords – A Safety Of Image File, The RSA Algorithm, Encryption, Descryption